Journal bearings subjected to dynamic loads: the analytical mobility method - Flores, Paulo (2005)
The main purpose of this work is to use the analytical mobility method to analyze journal bearings subjected to dynamic loads, with the intent to include it in a general computational program that has been developed for the dynamic analysis of general mechanical systems. A simple journal bearing subjected to a dynamic load is chosen as a demonstrative example, in order to provide the necessary results for a comprehensive discussion of the methodology presented.